Analysis of Non-Tax State Revenue on the Financial Performance of the Agricultural Quarantine Agency - Murti, Listyana Era; Gunarianto, Gunarianto; Mas'ud, Muchlis H (Jurnal Ilmu Ekonomi JIE, 2024)
This research aims to determine the difference between non-centralized and centralized PNBP receipts and realization at the Agricultural Quarantine Agency, the influence of the non-centralized system of PNBP on the financial performance of the Agricultural Quarantine Agency, and the influence of the centralized system of PNBP on the financial performance of the Agricultural Quarantine Agency. Data was collected by accessing audited financial reports and performance reports within the scope of the Agricultural Quarantine Agency for 2019 to 2022, data lag n-1, on 53 UPTs within the scope of the Agricultural Quarantine Agency as research objects. This research used a mixed methods approach, descriptive qualitative and quantitative. The results of this research conclude that there is a significant difference between the non-centralized system and the centralized system at the Agricultural Quarantine Agency, there is no significant influence between the non-centralized system PNBP on the Performance of the Agricultural Quarantine Agency. There is a significant and directly proportional influence between the centralized PNBP system and the Performance of the Agricultural Quarantine Agency.